2005
DOI: 10.1093/intimm/dxh340
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CD8 and TCR binding to Class I MHC ligands following T cell activation

Abstract: The capacity of T cells to bind peptide/MHC ligands changes with T cell development and differentiation. Here we study changes in peptide/MHC multimer binding following T cell activation. Surprisingly, T cell activation caused a marked reduction in specific peptide/MHC Class I multimer binding, which was distinct from transient TCR down-regulation, and was especially dramatic for engagement with low-affinity peptide/MHC ligands. Direct CD8-Class I interactions were also profoundly and rapidly impaired followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 51 publications
7
48
1
1
Order By: Relevance
“…We note that CD8 SP thymocytes and peripheral cells showed noticeably better noncognate binding above background than our earlier report (21) because of improvements in the methods used for preparation and storage of mutimers (see Materials and Methods and Ref. 42).…”
Section: Analysis Of Maturing Thymocytes Reveals Differences In Cd8 Nmentioning
confidence: 54%
See 3 more Smart Citations
“…We note that CD8 SP thymocytes and peripheral cells showed noticeably better noncognate binding above background than our earlier report (21) because of improvements in the methods used for preparation and storage of mutimers (see Materials and Methods and Ref. 42).…”
Section: Analysis Of Maturing Thymocytes Reveals Differences In Cd8 Nmentioning
confidence: 54%
“…Typically, multimer staining was performed at 4°C for at least 1 h in FACS buffer (PBS, 1% FCS, 0.02-0.2% azide) in the presence of the indicated anti-CD8␣ Abs, as described in detail previously (15). In some cases (where specified), multimer staining was performed at 4°C for 2 h in RP10 medium (RPMI 1640, 10% FCS with no azide), and stained for surface markers (including CD8) following washes: this staining protocol enhances weak CD8 noncognate multimer staining (42).…”
Section: Peptides and Mhc Multimersmentioning
confidence: 99%
See 2 more Smart Citations
“…As naïve T cells can effectively bind tetramers, events associated with activation may hinder tetramer binding 13. Indeed, several groups showed lack of tetramer binding on antigen‐specific T‐cell populations following activation 30, 31, 32, 33. One study reported that antigen‐specific T cells fail to bind tetramer following stimulation because of transient CD8 downregulation and altered CD8 glycosylation 30, 31.…”
Section: Discussionmentioning
confidence: 99%